How to Reduce the Crime Rate in Society? The Role of the Community Order Development Unit (Bintibmas) of Community Development Unit (Satbinmas) through Guidance and Counseling in Suppressing the Raise of the Crime of Two-Wheeled Vehicle Theft by the Garut Police Department - Iskandar Arya Buana (Advances in Police Science Research Journal, 2021)
The background of this research is because the criminal rate of two-wheeled motor vehicle theft is very high, so that the role of the bintibmas unit of the binmas unit is needed in suppressing the number of two-wheeled motorized theft crimes. The purpose of this study was to determine and describe the role played by the Garut Police in suppressing the crime of motor vehicle theft as well as supporting and inhibiting factors in preventing motor vehicle theft. This study uses management theory, 6M management elements, the concept of motor vehicle theft and the concept of socialization. This research uses a qualitative approach with a descriptive analysis method. The focus of this research discusses the role of the Community Order Guidance Unit (Bintibmas) in Guidance and Counseling in order to reduce the level of two-wheeled motor vehicle theft in the Garut Police jurisdiction. Collecting data by conducting interviews with several sources, observation and documentation study. Data analysis was performed by reducing data, displaying data and drawing conclusions. The results showed that 1) Lack of personnel resulting in accumulation of tasks 2) Facilities and infrastructure are damaged and not repaired 3) The method used is not in accordance with the prevailing era 4) Control is only a formality and once a month. The low economic capacity of the community and the high cost of living necessities make the perpetrators turn to criminal acts as a solution to life's problems. Suggestions addressed to related objects include equal distribution of personnel, improvement of personnel quality, control from the leadership, the use of methods adapted to the current era, as well as the renewal of damaged infrastructure.